Use of transcutaneous electrical acupoint stimulation in pulmonary surgery for patients with tuberculosis. (May 2022) - Xu, Lu-lu; Zhao, Wen-sheng; Li, Lang-ping; Du, Xin-dan
Abstract: Objective: This study aimed to analyze the effects of transcutaneous electrical acupoint stimulation (TEAS) on the immune function in patients with pulmonary tuberculosis (PT) and the inflammatory response following one-lung ventilation surgery by comparing the levels of inflammatory mediators, such as tumor necrosis factor alpha (TNF-α), interleukin 6 (IL-6), and interleukin 8 (IL-8); T lymphocyte subsets, including CD3 +, CD4 +, CD8 +, and CD4 + /CD8 + cells; and natural killer cells (NK cells). Methods: We randomly divided 62 patients who underwent general anesthesia for thoracotomy into two groups: TEAS and sham TEAS. Patients in the TEAS group underwent bilateral acupoint electrical stimulation at the Hou- Xi, Zhi- Gou, Nei- Guan, and He- Gu acupoints from 30 min before anesthesia induction until the end of surgery. TEAS was continuously maintained throughout the procedure with a dilatational wave at 2/100 Hz. Those in the sham TEAS group underwent the same management but without stimulation, and the anesthesia induction and maintenance methods were the same in both groups. Venous blood was drawn to monitor inflammatory mediators and lymphocyte subsets before anesthesia induction and 5 days after the surgery. Results: There was no statistical difference in the general conditions between the two groups ( P  > 0.05). Before anesthesia induction, the levels of inflammatory factors (IL-6, IL-8, and TNF-α), lymphocyte subsets (CD3 +, CD4 +, and CD4 + /CD8 + ), and NK cells did not statistically differ between the two groups ( P  > 0.05). Compared to the sham TEAS group, the levels of IL-6, IL-8, TNF-α, and CD8 + were lower in the TEAS group, while those of CD3 +, CD4 +, CD4 + /CD8 +, and NK cells were higher; however, only the change in TNF-α was significant ( P  < 0.05). Conclusion: TEAS at the Hou- Xi, Zhi- Gou, Nei- Guan, and He- Gu acupoints at 2 Hz/100 Hz can reduce the inflammatory response during one-lung ventilation but has no significant effect on the immune function in patients with tuberculosis.